Three-phase multilevel inverter for grid-connected distributed photovoltaic systems based in three three-phase two-level inverters. (1st November 2018) - Fernão Pires, V.; Cordeiro, A.; Foito, D.; Fernando Silva, J.
Highlights: A new triple inverter topology (T 3 VSI) with multilevel operation is proposed. Three isolated PV generators are used to feed each inverter. The solution allows to adapt classical multilevel Pulse Width Modulation (PWM) schemes. Increases of the maximum voltage applied to the isolation transformer. Abstract: A multilevel three-phase voltage source inverter (VSI) for distributed grid-connected photovoltaic system is proposed in this paper. This multilevel inverter is based on a new topology using three three-phase two-level VSIs (T 3 VSI) with isolation transformer. The photovoltaic panels are connected at the DC side of each three-phase VSI. The three-phase VSIs AC sides are connected to the three-phase isolation transformer with primary open-end windings, ensuring multilevel operation. The T 3 VSI can be modulated using existing multilevel Pulse Width Modulation (PWM) schemes. A control system designed to ensure the transfer of the energy generated by the PV generators to the grid is also presented, together with a Phase Disposition PWM (PDPWM) adapted for the multilevel T 3 VSI. Tests of the grid-connected PV multilevel T 3 VSI will be shown through simulation and experimental results. Several results obtained from experiments confirm the expected characteristics of the multilevel T 3 VSI photovoltaic system.